On Model-Consistent Expectations in Macroeconomics - Montes Rojas, Gabriel (2018)
In this paper we explore an alternative version of model- consistency of expectations, which allows the expectation- generating schemes to vary according to the state of accepted macroeconomic analysis. We perform an econometric exercise using standard existing models of different generations (built for the US economy) as potential expectations- forming tools. The discussion and implementation of alternative forms of model- consistency is the main purpose of the paper. As for the results, they suggest an absence of strong sensitivity to the expectations- generating schemes in past decades, while the performance of the models become problematic in recent times marked by the Great Recession.